Intra-osseous sclerosing epithelioid fibrosarcoma of the mandible: A case report and review of the literature - Joshua Allen; Daniel Hovander; Dolphine Oda; Erica Kao; Robert W. Ricciotti (Elsevier, 2021)
We report a rare case of sclerosing epithelioid fibrosarcoma (SEF) arising in the anterior mandible of a 49-year-old male confirmed by the detection of an EWSR1-CREB3L3 fusion gene. SEF of the oral cavity is rare. To our knowledge this case marks the twelfth reported case to date. Our report and review of the literature highlights the molecular, immunophenotypic, and unique clinicopathological features of SEF in the oral cavity, specifically, its predilection for the jaw bones. Although SEF is usually a malignancy of soft tissue, nine (75%) of the reported oral cavity cases have occurred as a primary jaw neoplasm. The mandible represents the most common location with seven cases, while two occurred in the maxilla. These findings suggest a propensity for bone involvement in the oral cavity, which may be a feature unique to this site.